FENOMENA HIJRAH ERA MILENIAL DAN SOSIAL MEDIA DALAM EKSPRESI KEBERAGAMAAN MENUJU MASYARAKAT MADANI (CIVIL SOCIETY ) DI KABUPATEN INDRAGIRI HULU PROPINSI RIAU - Juni Erpida Nasution (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2020)
Hijrah is a positive action to change a person's bad behavior to be better, or in Islamic religion means returning to fitraAllah SWTSWT, the current state of the millennial tends to be based on following trends so that the migration is limited to physical packaging or method dress is not essentially practiced properly, this happens because of the social media support factor that forces millennials to follow the trend directed by social media, considering that social media has become a life for millennials, if it does not follow trends on social media then his existence will not occur.